EFFECTIVENESS OF ASSESSING QUALITY OF LIFE IN WOMEN AFTER CONSERVATIVE MYOMECTOMY - Bekniyazova, D.A.; Mirzaeva, D.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. The presence of uterine fibroids and the need for conservative surgical removal significantly impact women’s mental and emotional well-being, presenting a crucial challenge in contemporary healthcare. Purpose. The aim of this study is to analyze the differences in quality of life experienced by women before and after undergoing a conservative myomectomy procedure, specifically focusing on women who are of reproductive age. Material and methods. Our study investigated the impact of conservative myomectomy on the well-being of 20 female patients, utilizing the UQOLS survey to assess their quality of life. Results. The study revealed significant differences in the health, career, emotional well-being, and intimate lives of participants with uterine fibroids. Notably, the overall quality of life score, as measured by the UQOLS, was considerably reduced in the fibroid group (67.69±2.58) compared to the healthy control group (82.73±2.34), demonstrating a statistically significant difference (p<0,001). Conclusion. Identifying the factors that contribute to a decline in quality of life and proactively addressing them can effectively prevent disease recurrences.